RULES ON MONETARY POLICY AND INTERNATIONAL IMPERFECT SUBSTITUTIONS OF ASSETS - Taufiq Carnegie Dawood (Faculty of Economics and Business, Universitas Malikussaleh, 2018)
This paper revisits and extend discussions which evaluate the impact of different rules on monetary policy. Rules on one which excludes or includes stability of the exchange rate as an objective of monetary policy making, with currency mismatch existence as given, on the fluctuations of major economic variables. In this paper I develop a financial accelerator model with financial intermediary consistent with currency mismatch, and assume imperfect international substitutability of assets. This paper found that the variation of rule of monetary policy considered in the analysis produces variations in the fluctuations of the macroeconomic variable. However the impact of the different monetary policy rules on the stability of the macroeconomic variables is shock dependent.